2018
DOI: 10.3390/buildings8080099
|View full text |Cite
|
Sign up to set email alerts
|

Shear Performance Assessment of Timber Log-House Walls under In-Plane Lateral Loads via Numerical and Analytical Modelling

Abstract: Log-house is an ancient construction technology based on the superposition of linear timber logs, connected to the orthogonal walls by a system of carvings, notches and corner joints. Due to the fact that this solution is widely used in constructions located in seismic or windy areas, the in-plane behaviour of walls represents an attractive research topic. In this paper, major outcomes of a Finite-Element (FE) numerical investigation carried out on single corner joints currently in use for log-house buildings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…Numerous researchers have studied these lateral resisting elements. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Firstly, various handcrafted notch geometries of corner joints (e.g., Saddle, Norwegian, Daimon, and Dovetail notch) were proposed and their performance was investigated under in-plane lateral loads. [7][8][9] Then, the lateral load resistance of the standard half lapped, and dovetail corner joints of modern log houses were examined via experiments, [10,12,13] numerical methods, [12][13][14][15] and analytical methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous researchers have studied these lateral resisting elements. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Firstly, various handcrafted notch geometries of corner joints (e.g., Saddle, Norwegian, Daimon, and Dovetail notch) were proposed and their performance was investigated under in-plane lateral loads. [7][8][9] Then, the lateral load resistance of the standard half lapped, and dovetail corner joints of modern log houses were examined via experiments, [10,12,13] numerical methods, [12][13][14][15] and analytical methods.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Then, the lateral load resistance of the standard half lapped, and dovetail corner joints of modern log houses were examined via experiments, [10,12,13] numerical methods, [12][13][14][15] and analytical methods. [16] In addition, the two main types of LF connections were investigated, including a sill log element on various floor types [7,17,18] and angle brackets. [10,11] In the case of log-log friction, the friction coefficients under various vertical loads and sliding characteristics between timber log layers were studied experimentally, [12,19] and it was found that the sliding characteristic between layers of log elements could not be included in the lateral load resistance prediction [10] because of its sensitivity to various parameters.…”
Section: Introductionmentioning
confidence: 99%
“…A simplified hybrid method has been presented for nonlinear FEM, particularly for timber frame buildings, such that the elements are modelled using the experimental testing results from the substructures [100]. Hybrid simulation has been utilized to investigate the seismic vulnerability of timber frame buildings [101][102][103][104][105][106][107][108][109], and then developed for numerical simulation of log houses [110][111][112][113][114][115] and post and beam structures [116][117][118][119][120][121].…”
Section: Seismic Vulnerability Assessmentmentioning
confidence: 99%
“…The governing material strength was assumed equal to the compressive resistance of spruce in the direction perpendicular to the grain, with f c,90 = 3.57 MPa the mean value. Spruce anisotropy was then accounted, in terms of resistance values, in the form of Hill plastic law (see [26,27]). The material density at 20 • C was finally set to the nominal value of 420 kg/m 3 .…”
Section: Mechanical Analysis In Fire Conditionsmentioning
confidence: 99%
“…This is the case of traditional structural solutions like log-house (or log-haus, or Blockhaus) systems that are not specifically considered by design codes (see for example [20,21]), particularly in fire conditions [22]. So far, research studies have been focused on their structural performance under various loading configurations, including seismic events [23][24][25][26][27], buckling [28] and thermal exposure [29].…”
Section: Introduction and State-of-the-artmentioning
confidence: 99%